Financial perfomance as a determinant of bank reputation: An empirical study from bank in ASEAN - Nyayu Khalilah Putri; Mohamad Adam; Isnurhadi; Mu'izzuddin (Postgraduate Program Merdeka University, 2026)
This study aims to analyze the relationship between financial performance indicators and bank reputation. An em-pirical approach is implemented using a sample of publicly listed banks, with financial data obtained from their an-nual reports. The analysis method used is statistical regression to test the effect of various financial performance indicators on bank reputation. The findings of the study indicate that both ROA and NPL do not have a significant effect on bank reputation. In contrast, NIM and BOPO show a positive relationship, meaning that profitability and operational efficiency can improve bank reputation. Moreover, DAR has a positive effect on bank reputation, indicating that higher leverage can reflect growth potential. However, DER has a negative effect on bank reputation, indicating that higher debt levels relative to equity can reduce stakeholder trust. In addition, LDR also has a negative effect on reputation, highlighting concerns related to liquidity risk. These findings provide important insights for banking institutions, indicating that effective financial performance management can strengthen their reputation and competitiveness in the market. This study contributes to the literature by employing Cumulative Abnormal Return (CAR) as a dynamic, market-based proxy for bank reputation, which is an approach that is relatively underutilized in ASEAN banking research. By capturing investor reactions to financial disclosures, this method offers a more responsive and nuanced measure of reputation than traditional indicators such as market value or brand perception.